2017
DOI: 10.1371/journal.pone.0180958
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study on association of proteasome subunit beta 8 (PSMB8) and transporter associated with antigen processing 1 (TAP1) polymorphisms and their transcript levels in vitiligo from Gujarat

Abstract: BackgroundAutoimmunity has been implicated in the destruction of melanocytes from vitiligo skin. Major histocompatibility complex (MHC) class-II linked genes proteasome subunit beta 8 (PSMB8) and transporter associated with antigen processing 1 (TAP1), involved in antigen processing and presentation have been reported to be associated with several autoimmune diseases including vitiligo.ObjectivesTo explore PSMB8 rs2071464 and TAP1 rs1135216 single nucleotide polymorphisms and to estimate the expression of PSMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Another SNP, in the LMP7 gene, not examined here, was associated with vitiligo in Indians from Gujarat [ 32 ], and a LMP2 SNP, also not tested by us, was found associated with vitiligo in Saudi Arabia [ 33 ]. For LMP7 rs2071543 , associated here with AD, it was reported that individuals with the TT genotype had a 3.5-fold higher ovarian cancer risk in Chinese people and 10-fold higher colon cancer risk in Germans than TG and GG genotypes [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another SNP, in the LMP7 gene, not examined here, was associated with vitiligo in Indians from Gujarat [ 32 ], and a LMP2 SNP, also not tested by us, was found associated with vitiligo in Saudi Arabia [ 33 ]. For LMP7 rs2071543 , associated here with AD, it was reported that individuals with the TT genotype had a 3.5-fold higher ovarian cancer risk in Chinese people and 10-fold higher colon cancer risk in Germans than TG and GG genotypes [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A little bit more is known on the TAP1 rs1135216 associations with diseases. The rs1135216*G (Gly637) allele was described to be strongly associated with vitiligo in a Saudi Arabian population [ 33 ], although not in Gujarati Indians [ 32 ]. It was also reported to increase the risk of pulmonary tuberculosis in Iranians [ 37 ], recurrent respiratory papillomatosis in Mexicans [ 38 ] and leprosy in Indians [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have identified potential genetic susceptibility loci in the genes involved in immunoregulation (CTLA4, NLRP1, MYG1, ICAM1, HLA), cytokines (TNFA, TNFB, IL4, IFNG, IL1B), antigen processing and presentation (PSMB8), redox homeostasis (SOD, CAT, GPX1) etc. to be associated with vitiligo susceptibility [42][43][44][45][46][47][48][49][50][51][52][53]. Homocysteine has gained a significant attention of researchers working on vitiligo since the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms include single-nucleotide polymorphisms (SNPs), nucleotide insertions, deletions, inversions and chromosomal translocations 9 10 . Many studies have identified that several SNPs, such as the NRF2 rs35652124 , PSMB8 rs2071464 and inducible nitric oxide synthase ( NOS2 ) gene polymorphism, were all associated with increased susceptibility to vitiligo 11 12 . Most SNPs could target promoter regions of genes that play critical regulatory roles in vitiligo pathogenesis.…”
Section: Pathogenesis Of Vitiligomentioning
confidence: 99%